TIPE KERIBADIAN DAN MODEL LINGKUNGAN DALAM PERSPEKTIF BIMBINGAN KARIER JOHN HOLLAND - Muslim Afandi (Sosial Budaya, 2011)
Many People who talk about careers that one of them is Jhon Holland. This characters believes that the success of a person/individual in the world and occupational careers are likely to be influenced by the type, nature and character of a certain psychological environment in which individuals are located. Compatibility between a particular type from the viewpoint of cetain psychological and environmental model also became the basis of capital and for individuals to develop and career. With a comprehensive study like this the the concept offered by Holland’s career received in many circles